Dynamics of the implementation of the protective role in the conduct of crimes: the practice of the Convention for the Protection of Human Rights and Fundamental Freedoms - Балобанова, Дар’я Олександрівна; Балобанова, Д. О.; Балобанова, Дарья Александровна; Balobanova, Daria O.; Balobanova, Dariia; Горбачова, Ірина Михайлівна; Горбачова, І. М.; Горбачева, Ирина Михайловна; Horbachova, Iryna M.; Gorbachova, Iryna; Оцяця, Анастасія Сергіївна; Оцяця, А. С.; et al. (Universidad del Zulia, 2020)
Criminal law offers the possibility of interfering with human life. To avoid such unjustified interference, society and the state must guarantee that human and civil rights are protected and that the standards established in the Convention for the Protection of Human Rights and Fundamental Freedoms are observed. Therefore, it is important to analyze the dynamics of the implementation of the protective function in the conviction of crimes in the interpretation of the European Court of Human Rights ECHR. In the methodological, he made of dialectics and documentary observation. The work aims to analyze the practice of the European Court of Human Rights, which tracks the dynamics of the protection function in sentencing for crimes. As a result of the study, the dynamics of the protection function in sentencing for criminal offenses were clarified through the practice of the ECHR, the problematic issues of the implementation of the protection function were analyzed in the example of Ukraine and foreign countries, and proposals were made, to use the practice of the ECHR as a “living tool” for the protection of human and civil rights and freedoms.

Кримінальне законодавство надає можливість втручання в життя людини. Щоб уникнути такого невиправданого втручання, суспільство та держава повинні гарантувати захист прав людини та громадянина та дотримання стандартів, встановлених Конвенцією про захист прав людини та основних свобод. Тому важливо проаналізувати динаміку реалізації захисної функції при засудженні за злочини у тлумаченні ЄСПЛ - Європейського суду з прав людини. У методологічному аспекті обрано діалектичний метод та документальне спостереження. Робота спрямована на аналіз практики Європейського суду з прав людини, який відстежує динаміку функції захисту при призначенні покарань за злочини. В результаті дослідження на практиці ЄСПЛ було з’ясовано динаміку функції захисту при призначенні покарань за кримінальні злочини, проаналізовано проблемні питання реалізації функції захисту на прикладі України та зарубіжних країн, а також були зроблені пропозиції щодо використання практики ЄСПЛ як «живого інструменту» для захисту прав і свобод людини і громадянина.

Уголовное законодательство предоставляет возможность вмешательства в жизнь человека. Чтобы избежать такого неоправданного вмешательства, общество и государство должны гарантировать защиту прав человека и гражданина и соблюдение стандартов, установленных Конвенцией о защите прав человека и основных свобод. Поэтому важно проанализировать динамику реализации защитной функции при осуждении за преступления в толковании ЕСПЧ - Европейского суда по правам человека. В методологическом аспекте избран диалектический метод и документальное наблюдение. Работа направлена ​​на анализ практики Европейского суда по правам человека, который отслеживает динамику функции защиты при назначении наказаний за преступления. В результате исследования на практике ЕСПЧ было выяснено динамику функции защиты при назначении наказаний за уголовные преступления, проанализированы проблемные вопросы реализации функции защиты на примере Украины и зарубежных стран, а также были сделаны предложения по использованию практики ЕСПЧ как «живого инструмента» для защиты прав и свобод человека и гражданина.
Balobanova D. Dynamics of the implementation of the protective role in the conduct of crimes: the practice of the Convention for the Protection of Human Rights and Fundamental Freedoms / D. Balobanova, I. Gorbachova, A. Otsyatsya, M. Dmytruk, A. Khylchenko // Cuestiones Políticas. – V. 38(67). – Universidad del Zulia, 2020. – P. 426-442.
Keywords: human rights protection function; criminal sentences; crimes; jurisprudence of the European Court of Human Rights; legal practice; функція захисту прав людини; кримінальні вироки; злочини; юриспруденція Європейського суду з прав людини; юридична практика; функция защиты прав человека; уголовные приговоры; преступления; юриспруденция Европейского суда по правам человека; юридическая практика; Research Subject Categories::LAW/JURISPRUDENCE